Iron Content as an Indicator for Legionella Species in Artificial Water Systems (Medico Legal Update, 2021)
Background: Legionella have emerged as a pathogenic group due to increased use and poor maintenanceof artificial water environments. World Health Organization considers Legionella associated diseases tobe underestimated, especially in developing countries due to difficulty in detection. The aim of this studywas isolation and culture of Legionella spp. from artificial water systems and to test the importance of ironconcentration which can be developed as a reliable chemical marker.Method: Thirty samples each were collected from drinking water coolers, cooling towers and shower headsfitted in different houses of Mangaluru city. Isolation and identification of the bacteria were carried out as perthe standard protocols followed by determination of iron content prescribed by IS 3025 (Part 53).Conclusion: Our study shows that concentrations of iron, is an important factor that increases the likelihoodof Legionella spp. Statistically, a concentration of 300 mg Fe/L shows a positive correlation with Legionellapresence. Therefore, monitoring suspect sites for iron concentration and chelation of available iron, canbe developed as respective assays for identifying Legionella spp. Furthermore, we show that PCR baseddetection of Legionella is a more robust method than the classical 3-plate method, especially for virulentstrains.